The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.fuel.2014.07.097
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur retention in an oxy-fuel bubbling fluidized bed combustor: Effect of coal rank, type of sorbent and O 2 /CO 2 ratio

Abstract: In this work, SO 2 retention via calcium-based sorbents added in a continuous bubbling 17 fluidized bed combustor (~3 kWth) operating in oxy-fuel combustion mode is analyzed. 18Tests were performed at different operating temperatures with three sorbents, two 19 limestones and one dolomite, and with three coals, ranging from lignite to anthracite, to 20 analyze the influence of coal rank, type of sorbent, sorbent particle size, and O 2 /CO 2 21 feeding ratio on the sulfation process. 22It was found that the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…5). Previous studies demonstrated that dolomites are able to reach high sulfation conversions, near 1 with respect to Ca content, both in calcining and noncalcining conditions during oxyfuel combustion in fluidized beds [24], as observed in Fig. 3.…”
Section: Effect Of Reaction Time On Product Layersupporting
confidence: 55%
“…5). Previous studies demonstrated that dolomites are able to reach high sulfation conversions, near 1 with respect to Ca content, both in calcining and noncalcining conditions during oxyfuel combustion in fluidized beds [24], as observed in Fig. 3.…”
Section: Effect Of Reaction Time On Product Layersupporting
confidence: 55%
“…There are several review papers (Buhre et al, 2005;Tan et al, 2005;Wall, 2007;Wall et al, 2009;Normann et al, 2009;Toftegaard et al, 2010;Davidson and Santos, 2010;Scheffknecht et al, 2011;Stanger and Wall, 2011;Chen et al, 2012;Lockwood, 2014) and books (Zheng, 2011;Toporov, 2014) published in the open literature. All of them have provided comprehensive information about the different aspects of oxy-PC combustion.…”
Section: Oxy-pc Power Plantmentioning
confidence: 99%
“…Simplified schematic flow diagram of oxy-PC coal fired power plant with CO2 capture, including possible locations for flue gas recirculation and O2 addition -adapted fromDavidson and Santos (2010).…”
mentioning
confidence: 99%
“…Conversely, the N 2 O emission decreased with the increase in operating temperature. In a subsequent study, de las Obras‐Loscertales et al evaluated SO 2 retention by three different calcium‐based sorbents (a dolomite and two limestones). Tests were respectively performed with three different coal types (lignite, bituminous and anthracite) at different operating temperatures to evaluate the influence of sorbent type and particle size, coal rank, temperature and O 2 /CO 2 feed ratios on sulfation.…”
Section: Oxy Combustion In Fluidized Bedsmentioning
confidence: 99%
“…De las Obras‐Loscertales et al reported experimental results conducted in a 3 kWth BFB furnace under oxy‐combustion atmosphere, where sulfur retention through Ca‐based sorbents and the influence of coal rank were studied. The limestone was observed to have a greater sulfur retention capability when combustion temperature was increased to about 925 °C.…”
Section: Design and Operational Issuesmentioning
confidence: 99%